Efektifitas Filter Carbon Aktif dalam Menurunkan Kadar Mangan (Mn) dan Besi (Fe) dalam Air Tanah Puskesmas Kelapa Dua Kabupaten Tangerang - Ati Sri Wahyuni (JURNAL TECHLINK, 2019)
Water is the most important requirement for living things. Humans and other living things are very dependent on water to sustain their lives. Based on the results of external supervision carried out by the District Health Office. Tangerang in 2016 found the quality of clean water at Kelapa Dua Health Center containing Mn and Fe with levels that exceeded the quality standard. Based on Permenkes 416 of 1990, Manganese (Mn) levels in permissible drinking water is 0.5 mg / lt, Iron (Fe) 1.0 mg / lt, In this Data Analysis Technique including data processing techniques carried out by linear regression of data set as research variables. Based on the results, the following conclusions are obtained, Efficiency of activated carbon media with a media thickness of 90 cm in reducing Fe content in water by 39.38%, Efficiency of activated carbon media with a media thickness of 90 cm in reducing Mn content in water by 81.82%. There is a Significant Effect of Filtration Treatment on Fe, and Mn Content. The thicker the filtration media, the better degradation of Fe, and Mn.